MATHEMATICAL CRITICAL THINKING SKILLS OF VOCATIONAL HIGH SCHOOL STUDENTS IN SOLVING AKM PROBLEMS BASED ON PERSONALITY TYPE - Dea Oktaviani; Dwi Yulianto; Susilo, Yusup Junaedi (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research is motivated by the low critical thinking and mathematical problem-solving skills of vocational school students in Lebak-Banten Regency, especially in solving AKM problems seen from the field of expertise and personality type. Vocational High School (SMK) students are students who are required to become work-ready graduates who are not only technically skilled, but also must have good critical thinking and problem-solving skills. The purpose of this study is to find out: 1) the relationship between areas of expertise and personality types on the mathematical critical thinking ability of vocational school students in solving AKM problems; and 2) the influence between personality areas and personality types on the mathematical critical thinking ability of vocational school students in solving AKM problems. The method of this research is a quantitative descriptive type of cross sectional survey. The population in this study was 8,577 students from 69 public and private schools which were grouped based on 9 areas of expertise and 4 personality types of vocational school students in Lebak-Banten Regency. Data collection in this study was through questionnaires, students' mathematical critical thinking ability tests, and interviews. The data analysis techniques used in this study are descriptive statistics and inferential statistics. The results in this study show that; 1) there is a relationship between personality type and mathematical critical thinking ability of vocational school students in solving AKM problems; and 2) the influence between personality types on the mathematical critical thinking ability of vocational school students in solving AKM problems.